Автоколивальні процеси подрібнення в барабанних млинах - Дейнека, К. Ю. (НТУ "ХПІ", 2014)
Розглянуто явище самозбудження автоколивань завантаження в робочій камері барабанного млина. З’ясовано вплив швидкості обертання на амплітуду коливань. Оцінено вплив автоколиваних процесів на продуктивність та енергетичну ефективність помелу.

The phenomenon of filling pulsations self-oscillations in tumbling mill working chamber is considered. The effect of rotational speed on the amplitude of oscillation is found. The influence self-oscillations processes for performance and energy efficiency of grinding is estimated.
The oscillating grinding process in tumbling mill
Keywords: внутрішньокамерне завантаження; автоколивання; самозбудження; швидкість обертання; демпфуючий вплив; ефективність помелу; tumbling mill; intrachamber filling; self-oscillations; elf-excitation; rotational speed; damping effect; efficiency of grinding